Reduction of Power Fluctuations of a Large-Scale Grid-Connected Offshore Wind Farm Using a Variable Frequency Transformer - Wang, Li; Chen, Long-Yi (IEEE transactions on sustainable energy, 2011)
This paper presents a novel control scheme using a variable frequency transformer (VFT) of 100 MW to effectively reduce power fluctuations of an equivalent 80-MW aggregated doubly-fed induction generator (DFIG)-based offshore wind farm (OWF) connected to an onshore 120-kV utility grid. The q-d axis equivalent-circuit model is employed to establish the mathematical models for the VFT and the OWF to derive the complete dynamic equations of the studied system under three-phase balanced conditions. A frequency-domain approach based on a linearized system model using eigen techniques and a time-domain scheme based on a nonlinear system model subject to disturbance conditions are both performed to examine the effectiveness of the proposed control scheme. It can be concluded from the simulation results that the proposed VFT is effective to smooth the fluctuating active power of the OWF injected into the power grid while the damping of the studied OWF can also be improved.